Anxiety, distress, and pain in pediatric urodynamics. Issue 4 (23rd March 2020) - Finkelstein, Julia B.; Cahill, Dylan; Graber, Kelsey; Tulley, Kelsey; O'Connell, Brianna; Mednick, Lauren; Rosoff, James S.; Bauer, Stuart B.; Weinstock, Peter; Estrada, Carlos R.
Abstract: Aims: No one has assessed urodynamic studies (UDS) to determine those steps that elicit the greatest anxiety, distress, and pain in children. We sought to systematically evaluate a child's UDS experience to mollify these reactions. Methods: Prospective study involving children aged ≥5 undergoing UDS over a 6‐month period (from 10 December 2018 to 22 May 2019). Upon arrival, patients completed a visual analog scale for anxiety (VAS‐A, 0‐10) about the upcoming procedure. A research assistant assessed the patient's behavior during each major step of UDS using a validated brief behavioral distress scale. Nursing staff also obtained patients' pain ratings (0‐10) for these key elements. Immediately after UDS, each child completed a posttest VAS‐A along with a survey about the UDS experience. Results: A total of 76 UDS were observed; almost half included sphincter needle electromyography (EMG). Mean patient VAS‐A scores were 2.3 before UDS, compared to 0.8 afterward ( P < .001). The highest proportion of distressful behaviors were observed during EMG needle (31%) and urethral catheter (29%) insertion, in agreement with the highest mean pain scores of 3.2 and 2.7, respectively. Fifty‐four percent of children reported not being completely aware of what was going to happen before the procedure and 50% of those patients exhibited at least one interfering or potentially interfering behavior. Similarly, 60% of children with no prior history of UDS exhibited at least one interfering or potentially interfering behavior. Conclusions: EMG needle and urethral catheter placement, initial urodynamic testing and not knowing what to expect were associated with greater pain and distress during pediatric UDS.